Dispersion over the business cycle: Passthrough, productivity, and demand? - Mikael Carlsson; Alex Clymo; Knut-Eric Joslin (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2023)
We characterize the dispersion of firm-level productivity and demand shocks over the business cycle using Swedish microdata including prices and analyse the consequences for firms and the aggregate economy. Demand dispersion increases by more than productivity dispersion in recessions. Productivity shocks pass through incompletely to prices and have limited effect on sales dispersion. Demand shocks explain most of the variation in sales dispersion. In a heterogeneous-firm model matching the micro facts, demand dispersion has unambiguously negative effects on output via increased uncertainty and a "wait and see" channel. Productivity dispersion does not generate "wait and see" effects, but affects output negatively by inducing markup dispersion.
Keywords: D21; D22; D81; E32; L11; 330; demand estimation; productivity; variable markups; business cycles; dispersion; uncertainty; passthrough; adjustment costs